2011
DOI: 10.2214/ajr.10.5483
|View full text |Cite
|
Sign up to set email alerts
|

Does the Type of Intrauterine Device Affect Conspicuity on 2D and 3D Ultrasound?

Abstract: The levonorgestrel-releasing IUD is significantly less conspicuous than the copper IUD on 2D imaging. Three-dimensional ultrasound enhances the conspicuity of both types of IUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 10 publications
1
29
0
3
Order By: Relevance
“…Other studies have shown that copper IUDs are easier to visualise with ultrasound, whereas imaging of Mirena IUDs is not as accurate and requires higher operator skill. 6,14,15 All of the indeterminately positioned IUDs shown in Figure 2 were Mirena IUDs and were inadequately visualised due to poor echogenicity and partial views of the device. Valsky et al 16 found that the IUD acoustic shadow on the 3D-reconstructed coronal image can give a good clue to its location.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that copper IUDs are easier to visualise with ultrasound, whereas imaging of Mirena IUDs is not as accurate and requires higher operator skill. 6,14,15 All of the indeterminately positioned IUDs shown in Figure 2 were Mirena IUDs and were inadequately visualised due to poor echogenicity and partial views of the device. Valsky et al 16 found that the IUD acoustic shadow on the 3D-reconstructed coronal image can give a good clue to its location.…”
Section: Discussionmentioning
confidence: 99%
“…In a significant number of these complaints, 23% and 38%, respectively, the IUD was found to be malpositioned. Bleeding disturbances were found to be more predictive of malposition [9].…”
Section: Does a Malpositioned Or Displaced Iud Cause More Side Effects?mentioning
confidence: 91%
“…• After implantation, may occur some complications: 5 -Menstrual disorders -Pelvic pain -Dysmenorrhea -Migration -Infections -Pelvic inflammatory disease -Perforation of the uterus -Pregnancy (Fig. 1).…”
Section: 5005/jp-journals-10009-1365mentioning
confidence: 99%
“…5,[9][10][11] In fact, usually only the proximal and distal ends of the shafts and a central shadow of the intersection of the stem and arms can be seen in the sagittal and transverse planes. • However, three-dimensional (3D) US appears recently to be more useful 9 because it uses a volume rendering which contains the whole uterus with the IUD.…”
Section: 5005/jp-journals-10009-1365mentioning
confidence: 99%